1962
DOI: 10.1063/1.1728675
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocrystalline Anisotropy of Rare-Earth Iron Garnets

Abstract: This paI:er will review recent anisotropy data, deduced from static and resonance measurements, on the r:u-e-earth lron ga:nets of formula 5Fe2C?a 3M20 3, where M i~ Y, Gd, Vb, Er, Sm, Tb, Dy, and Ho, respectively. Both the hIgh temperature behavlOr (up to 300 0 K) whIch can be expressed in terms of the anisotropy const~nts KI a.r:d K2 and the ~nomalous ~nisotropy properties which occur at liquid helium temperatures are dl.scussed. 'Ihe results are mterpreted III terms of the single ion model which considers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…There is also a growth-induced anisotropy as a result of two nonequivalent dodecahedral position selective filling [10]. Magnetostrictive anisotropy is a result of reverse magnetostrictive effect at the he presence of mechanical stresses [11].…”
Section: Magnetic Anisotropymentioning
confidence: 99%
“…There is also a growth-induced anisotropy as a result of two nonequivalent dodecahedral position selective filling [10]. Magnetostrictive anisotropy is a result of reverse magnetostrictive effect at the he presence of mechanical stresses [11].…”
Section: Magnetic Anisotropymentioning
confidence: 99%
“…The temperature dependence of K 1 for Ce:YIG has not been reported, but other rare earth iron garnets show large increases in K 1 on cooling as mentioned above. 25,26 The shape anisotropy scales with the square of saturation magnetization and therefore also increases on cooling. However, this increase is modest: M(195 • C)/M(25 • C) = 1.33 based on our VSM data, which compares well to a published value of 1.4.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…There are little data on magnetocrystalline anisotropy or magnetostriction of Ce:YIG, but rare earth iron garnets typically show a monotonic increase of the magnetocrystalline anisotropy by a factor of 5-50 and an increase in magnetostriction coefficients by a factor of 2-5 when cooled down from RT to liquid nitrogen temperatures. 25,26 Previous studies of the magnetostriction of Ce:YIG show that Ce 3+ ions contribute to a positive magnetostrictive coefficient. However, the investigations are limited to small Ce concentrations.…”
mentioning
confidence: 99%
“…5 It was deduced that the K 1 value would then reach the value of + 3.0 x 10 6 in the limit of 0 K. 5 In this type of material the Sm 3+ ion has been reported to contribute a moment of 0.14 µB at approximately 0 K (the measured range was reported to be 1.4 K-298 K) to the net magnetization. 4,5 In addition previous works have shown that temperature dependent magnetization measurements exhibited a minimum at about 35 K resulting from the large anisotropy caused by the Sm 3+ ion. 4 Rare-earth garnet-structure ferrites materials are generally prepared through chemical methods in the form of submicron to nano-crystalline particles.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In particular the ferrimagnet samarium-iron garnet (Sm 3 Fe 5 O 12 ) has become of wide interest due to its large anisotropy with the anisotropy constants of K 1 : -1.2 x 10 6 ergs cm −3 and K 2 : + 1.0 x 10 6 ergs cm −3 (at 80 K) induced by the presence of the Sm 3+ ion. 5 It was deduced that the K 1 value would then reach the value of + 3.0 x 10 6 in the limit of 0 K. 5 In this type of material the Sm 3+ ion has been reported to contribute a moment of 0.14 µB at approximately 0 K (the measured range was reported to be 1.4 K-298 K) to the net magnetization. 4,5 In addition previous works have shown that temperature dependent magnetization measurements exhibited a minimum at about 35 K resulting from the large anisotropy caused by the Sm 3+ ion.…”
Section: Introductionmentioning
confidence: 99%